Design and experimental characterization of a combined WPT–PLC system. Issue 2 (21st November 2017) - Barmada, Sami; Dionigi, Marco; Mezzanotte, Paolo; Tucci, Mauro
Abstract : In this contribution, the authors perform the design and show the experimental results relative to a prototype of a combined wireless power transfer (WPT)–power line communications (PLC) system, in which the WPT channel is interfaced to a PLC environment to allow data transfer when the cabled connection is no longer available. The main rationale behind this idea stays in the fact that PLC communication is now a popular choice to enable communications, for instance, in smart grids and in home automation, while WPT devices start to be available in the market (i.e. for mobile phones) and soon they will be a reality also for higher power (i.e. vehicle battery charging). In particular, theoretical insights about the requirements of the system are given; a two coils system has been implemented and a measurement campaign, together with simulations, show that the system is of great potentiality and could be used in applications where both wireless power and data transfer are needed (such as vehicles battery charging), achieving maximum power transfer and good data rate in order to transmit high-speed signals.